HUBUNGAN KASUS HERNIA INGUINALIS LATERALIS DENGAN DESCENSUS TESTIS PERSPEKTIF KASUS DI DIVISI BEDAH ANAK RSUD ARIFIN ACHMAD PEKANBARU PERIODE JANUARI 2011 - DESEMBER 2013 - Megasari, Elia; Wahid, TB Odih Rhomdani; Lestari, Siti Mona Amelia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Lateral inguinal hernia is the most common type of discovered hernia, a state where most of the intestinal went through the internal ring to the inguinal canal. In the testicular descent process trailed the processus vaginalis, in neonates more or less about 90% of the processus vaginalis remains open, whereas in one year old infants about 30% of the processus vaginalis has not been closed yet. This study is a retrospective analytic study using primary data in the form of a medical record with total sampling method to determine the corellation of the lateral inguinal hernia with testis descensus in General Hospital Arifin Achmad Pekanbaru Pediatric Surgery Division. Samples were obtained as many as 105 people, taken from medical records in the medical record installation General Hospital Arifin Achmad Pekanbaru from January 2011 - December 2013. Results showed that the majority of complaints arise age began at age > 1 year - 5 years a total of 33 patients (31,43%), most of patients achieved lateral inguinal hernia at age > 1 year - 5 years were 61 patients (58.09%), and none of prematurity patients (0%). About 99 patients (94%) experienced a lateral inguinal hernia and 6 patients (5.71%) did not experience lateral inguinal hernia, and mostly on the dexstra were 60 patients (60.61%). The result of the statistic test Kolmogorov Smirnov was p value = 0.000. Conclusion on this research was: there is a relation between lateral inguinal hernia with testicular descensus.Keywords: lateral inguinal hernia, testicular descensus, children